Analisis religiusitas, halal brand personality dan norma subyektif terhadap keputusan pembelian kosmetik pada Remaja di Kota Purwokerto - Muchammad Agung Miftahuddin; Ugung Dwi Aryo Wibowo; Alfalisyado . Alfalisyado (University of Darussalam Gontor, 2020)
This study aimed to examine the influence of religiosity, halal brand personality and subjective norms on the decision to buy cosmetics for adolescents in the city of Purwokerto. The study population was adolescents aged 17-25 years. A sample of 100 people was taken using purposive sampling method. Hypothesis testing was carried out by structural equation modeling (SEM) PLS version 2.0. The results of the analysis indicate that religiosity, Halal Brand Personality and Subjective Norms have a significant effect on cosmetic purchasing decisions among adolescents in Purwokerto.